Palmito (Bactris gasipaes H.B.K.) cultivation in the Atlantic and Northern Zone of Costa Rica - Roeland, R. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
51 pág, ilus, tab, 17 ref. También como: Field Report - Atlantic Zone Programme (CATIE) no. 119